NORMA PRIBADI DAN KEPATUHAN WAJIB PAJAK: APAKAH KEPERCAYAAN PADA PEMERINTAH BERPERAN? (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
The purpose of this study was to analyze the effect of personal norms and trust in the government on taxpayer compliance. In addition, this study also aims to analyze whether trust in the government mediates the effect of personal norms on taxpayer compliance. The population of this study is individual taxpayers in Kalimantan, while the sample of this study is individual taxpayers who are registered at the Central Kalimantan tax office. Sampling used purposive sampling, with the criteria of individual taxpayers having a Taxpayer Identification Number. Data was collected by distributing questionnaires with the help of social networks. Data analysis technique uses Partial Least Square (PLS) with the help of WarpPLS. Respondents in this study amounted to 104 respondents. This study obtained the results that individual taxpayer compliance was influenced by personal norms and trust in the government, but trust in the government did not mediate the effect of personal norms on taxpayer compliance.